Exploring hybridity the rise of "Cordilleran cinema" in the digital age - Dasalla, Jonnie Lyn P.
The study explores how the rise of Igorot film productions in the digital age shapes the notion of “Cordilleran Cinema.” The democratization of digital technology advances the growth of local regional film productions, providing new perspectives and narratives from the indigenous community. This phenomenon alters the current landscape of Philippine Cinema, which is predominantly centralized in Metro Manila.